How Nutrition and Sanitation Shape Toddler Development: A Closer Look at Health Risk Factors - Apriliani, Anindya Aurora; Lestari, Nining; Triastuti, N. Juni; Candrasari, Anika (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2024)
Purpose: Toddler development is a condition of change in the form and function of organ and individual maturation. Under-five developmental disorders are still a case that requires special attention. The first 1000 days of a child's birth is the golden period for child development. Based on data Kemenkes in 2021 shows that there are 7,512.6 per 100,000 population (7.51%) of toddlers in Indonesia who experience developmental disorders. There are several factors that influence development, including nutritional status and family environmental sanitation. Nutritional status as measured by Body Mass Index (BMI) affects the development of toddlers. The relationship with nutritional status, if the nutritional status is poor then it becomes a factor that further disrupts the physical development of toddlers with optimal nutritional status. Methodology: This study used a analytic design, with a cross-sectional approach. Sampling using fixed disease sampling method from Development Pre-Screening Questionnaire and Clean and Healthy Living Behavior questionnaire data and medical records of toddlers at Gatak Health Center. Data analysis using the chi-square test with SPSS 25. The sample size used was 91 samples. Results: The results of chi-square nutritional status with the development of toddlers obtained OR = 6.618 (with p = 0.050). While the relationship between family environmental sanitation with the development of toddlers obtained OR 5.661 (with p=0.022). Conclusion: Nutritional status and environmental sanitation are significantly associated with the development of toddlers.